COST CALCULATION ANALYSIS THROUGH ACTIVITY-BASED COSTING APPROACH IN THE VILLAGE UNIT COOPERATIVE (A Case Study at â€œKUD DAUâ€ Malang) - Pratikto, Nurhendro Yoga (Jurnal Ilmiah Mahasiswa FEB, 2017)
The study aims to analyze how cost calculation is carried out in the Milk Processing Unit of KUD-DAU and examine what if the calculation employs activity-based cost calculation for cost analysis, cost reporting, and decision making. The essential idea lies on the comparison between conventional cost accounting system and the activity- based costing (ABC). The result of the study shows that the conventional cost calculation method applied by the KUD has emerged a variance of different value to the cost calculated through the ABC method. The use of ABC method shows that the UPS KUD-DAU over-calculates pasteurized milk products in 140ml and 200ml cups, and under-calculates the pasteurized milk products in 1 Lt and 600ml bottles, fresh bulk, flavored bulk, and plain bulk. The use of ABC method enables the unit to estimate the overhead cost of the consumed products more accurately rather than the conventional one does because the conventional method charges the overhead directly on the product without exploring the activity causing such an overhead. The use of ABC method is, therefore, recommended to assist the KUD-DAU UPS management in making the right decision and improving performance in production activities in order to achieve the best level of effectiveness and efficiency. Keywords: Conventional Method, Activity-based Costing, Activity Costs, Production Costs